Linking earnings management practices and corporate governance system with the firms' financial performance: A study of Indian commercial banks. Issue 2 (2nd May 2017) - Kumari, Prity; Pattanayak, Jamini Kanta
Abstract : Purpose: In the shadow of global financial crisis, practice of earnings management can be hazardous for the growth and development of an economy, especially for a developing economy like India. This empirical study is performed to analyse the presence of earnings management practices in Indian public and private commercial banking industry. This study also aims at developing a framework for the three-way relationship existing between the variables of corporate governance, earnings management practices and firm performance. Design/methodology/approach: Data have been collected for a period of 11 financial years (2003-2013) from Prowess (Centre for Monitoring Indian Economy) 4.14 database. A bank-based accrual model has been used for calculating earnings management practices. OLS regression has been used for analysing degree of interdependence among variables of corporate governance, earnings management practices and financial performance. Findings: The analysis supports the fact that there is the existence of income increasing earnings management practices in Indian commercial banks. It is also observed that corporate government practices (viz. board characteristics, audit practices and performance-based remuneration) basically work as restricting variables for earnings management practices. It is evident from the analysis that market-based firm performance variables (viz. PE ratio, yield and profit after tax) are significantly related to earnings management and corporate governance system. Practical implications: The finding of this study will help in monitoring and controlling fraudulent earnings management practices existing in Indian commercial banks. Originality/value: This study is the initial research about the presence of earnings management practices in Indian commercial banks.